The Influence of Religiosity on The Consumptive Behavior of Muslim Individuals in Indonesia Based on IFLS-5 Data - Nurul Fathia, Raina; Hermawan, Wawan (Universitas Negeri Medan, 2025)
This study aims to analyze the influence of religiosity on Muslim individuals' consumptive behavior in Indonesia. The data used is sourced from the Indonesia Family Life Survey (IFLS) wave 5 in 2014, with a sample of 2,986 Muslim respondents aged minimum 19 years. The analysis method employed is multiple linear regression with religiosity as the main independent variable, while gender, income, and age serve as control variables. The results show that religiosity has a negative and significant effect on consumptive behavior. The control variables of gender and income also show significant effects, while age does not have a significant influence.